Upaya intensifikasi dan ekstensfikasi pajak dalam meningkatkan pendapatan asli daerah di Kabupaten Maluku Tengah - Silooy, Revy Wilhelmina; Latuamury, Jabida; Sapulette, Shella Gilby (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to analyze and identify the increase in local indigenous income through the intensification and extensification of regional taxes and levies in the central Maluku regency. This research uses a descriptive qualitative approach using case studies. The analysis uses a qualitative descriptive method with sampling techniques using purposive sampling through interviews, observation and documentation studies, and data validity using data triangulation. The results showed that efforts to intensify regional taxes through institutional aspects, regulations, and personnel aspects during the Covid-19 pandemic showed a trend of increasing regional original income and improving the quality of tax management resources. Meanwhile, efforts to exaggerate local taxes through the creation and data collection of sources of provincial taxes and potential regional levies, as well as investment policies through the use of assets, increase the original income of the Central Maluku Regency government area.